Research in organizational change and development. Vol. 14 - Woodman, Richard W.; Pasmore, William A. (Emerald, 2003)
Part of a series presenting scholarly thinking about research and concepts related to the transformation of organizations. As in previous volumes in the series, contributors provide comprehensive literature reviews, methodological breakthroughs, and cutting edge theories. The papers presented in Volume 14 address practical, conceptual and methodological issues in the field of organizational change. They offer a categorization scheme for interventions; an analysis of the importance of different change drivers in complex interventions; a call for greater attention to structure-process dualities; suggestions for making change more lasting; a new approach to measuring organizational culture based on shared schema; a field study of organizational learning; and an alternative approach to measuring experienced change.
Keywords: Business & Economics -- Organizational Behavior.; Psychology -- Applied Psychology.; Organizational theory & behaviour.; Organizational change.; elektronické knihy; electronic books